A Preliminary Study on the International Spread of the Culture of Yu the Great: - Wu, Jianping (Pacific International Journal, 2024)
Yu the Great is a flood control hero and the founding king of the Xia Dynasty. The Culture of Yu the Great is the source of Chinese culture, which has been passed down and developed for thousands of years and has a profound influence both domestically and internationally. With the further expansion of the influence of Chinese classic culture, the international spread of the culture of Yu the Great has also attracted increasing attention. The recognition of the culture of Yu the Great by Japan in East Asia can be traced back to a thousand years ago. In recent years, researches on cultural relics of Yu the Great have become elaborate. Descendants of Yu the Great in South Korea have thrived for generations. The English speaking world has also conducted research on the culture of Yu the Great. The paper gathers the wisdom of scholars at home and abroad to commemorate virtues of Yu the Great, which is of great significance.